2018
DOI: 10.1242/jeb.179085
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear amplification of graded voltage signals in the first-order visual interneurons of the butterflyPapilio xuthus

Abstract: Lamina monopolar cells (LMCs) are the first-order visual interneurons of insects and crustacea, primarily involved in achromatic vision. Here, we investigated morphological and electrophysiological properties of LMCs in the butterfly Using intracellular recording coupled with dye injection, we found two types of LMCs. Cells with roundish terminals near the distal surface of the medulla demonstrating no or small depolarizing spikes were classified as L1/2. Cells with elongated terminals deep in the medulla that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In our previous study, we reported that depolarizing offspikes could be recorded in some Papilio LMCs (Rusanen et al 2018). However, we found that the off-spike generation was an unstable trait, presumably related to the Naka-Rushton function: For typical LMCs, the exponential slope n is 1.02 and the stimulus intensity eliciting 50% V max (logK) is − 2.68; for slow LMC-like units n = 0.47 and logK = − 0.4; and for extracellular potential n = 0.54 and logK = − 1.01. k Latencies (i.e., time taken for the membrane potential to reach its peak) of hyperpolarizing ontransients under different light intensities for typical LMCs (N = 31), slow LMC-like units (N = 13), and extracellular potentials (N = 5).…”
Section: Identification Of Lamina Monopolar Cell (Lmc) Responsesmentioning
confidence: 92%
“…In our previous study, we reported that depolarizing offspikes could be recorded in some Papilio LMCs (Rusanen et al 2018). However, we found that the off-spike generation was an unstable trait, presumably related to the Naka-Rushton function: For typical LMCs, the exponential slope n is 1.02 and the stimulus intensity eliciting 50% V max (logK) is − 2.68; for slow LMC-like units n = 0.47 and logK = − 0.4; and for extracellular potential n = 0.54 and logK = − 1.01. k Latencies (i.e., time taken for the membrane potential to reach its peak) of hyperpolarizing ontransients under different light intensities for typical LMCs (N = 31), slow LMC-like units (N = 13), and extracellular potentials (N = 5).…”
Section: Identification Of Lamina Monopolar Cell (Lmc) Responsesmentioning
confidence: 92%
“…Physiologically different LMC subtypes have been described in different species. For example, LMCs in bumblebees and butterflies exhibit sustained components [50,51], and motionsensitive neurons perform better than photoreceptor responses predict in the nocturnal hawkmoth [32,52]. Interestingly, presynaptic L2 and L3 calcium signals are highly reminiscent of sustained and transient calcium signals in bipolar cells of the vertebrate retina [53][54][55].…”
Section: A Role For Luminance In Image Processing Might Be a Common Fmentioning
confidence: 99%
“…Situation is similar in Papilio , where PxHCLA immunoreactivity is found in the medulla layers 2, 4, 5a, and 6–8 (Figure a,c). The layer 4 contains histamine‐containing lvf terminals (Hamanaka et al, ) as well as terminals of some LMCs (Ribi, ; Rusanen, Frolov, Weckström, Kinoshita, & Arikawa, ). Therefore, those PxHCLA‐positive cells may be LMCs.…”
Section: Discussionmentioning
confidence: 99%